Autoimmune glial fibrillary acidic protein astrocytopathy complicated with low flow perimedullary arteriovenous fistula: a case report - Xu, Ting; Chen, Jingyun; Xuan, Tingting; Cheng, Jiang; Li, Haining (Frontiers in Immunology, 2023)
Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy and low-flow perimedullary arteriovenous fistulas (PMAVFs) may cause longitudinal widespread myelopathy. We report a middle-aged male patient with autoimmune GFAP astrocytopathy complicated with low flow PMAVFs disease, presenting with lower extremity weakness and dysuria. Magnetic resonance imaging (MRI) of the spinal cord revealed a significant longitudinal extent of T2 high signal from T11 to L1, with the lesion located proximal to the vascular territory supplied by the anterior spinal artery. Multiple patchy abnormal signals were seen adjacent to the anterior and posterior horns of the lateral ventricles bilaterally and at the centers of the semi-ovals on MRI of the cranial brain, with iso signal in T1Flair, the high signal in T2WI, and no high signal seen in Diffusion Weighted Imaging (DWI). Subsequently, the presence of anti-GFAP antibodies was detected in the cerebrospinal fluid (CSF), and the diagnosis of autoimmune GFAP astrocytopathy in conjunction with low-flow PMAVFs was confirmed through spinal digital subtraction angiography (DSA). This case report aims to increase neurologists’ awareness of this disease and avoid missed or misdiagnosed cases that may lead to delayed treatment.